Breaking the Chains of Poverty: Capitalistic Relations and Leisure Time Patterns Among Fishermen in Tanjungbalai - Afrida Afrida; Jonson Handrian Ginting (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study investigates the persistent poverty among fishing communities in Tanjungbalai City, North Sumatra, using an ethnographic qualitative approach. Despite Tanjungbalai’s status as a leading national anchovy producer, its fishers remain impoverished due to systemic dependence on middlemen, monopolized market access, and a lack of financial and infrastructural support. The study involved 26 purposively selected respondents, including traditional fishermen, fishermen's wives, and tekong (boat captains), ensuring a representative perspective. Findings reveal that those capitalistic dynamics in the fish production process—characterized by middlemen's control over capital and distribution—compel fishers to sell their catches at prices below market value, creating a cycle of indebtedness and economic instability—additionally, unproductive leisure activities such as gambling, nightlife, and drug use further hinder financial independence. The study suggests a combination of economic and social interventions to address this issue, including fair market access, financial literacy programs, and alternative income-generating activities. Strengthening fisher cooperatives and providing microfinance opportunities can help reduce dependency on middlemen. The research highlights how structural economic exploitation and leisure patterns entrench poverty, necessitating integrated policy measures and community-based solutions.